Generational Motivation in Sustainable HR Management - Habil, Szilárd Malatyinszki (Journal of Cultural Analysis and Social Change, 2025)
Today, sustainability extends beyond its traditional environmental and economic interpretations and has become a key issue within human resource management as well. The long-term success and competitiveness of organizations increasingly rely on their ability to retain, develop, and motivate employees, with special emphasis on effectively managing generational differences. This study aims to investigate how the intentional development of managerial tools can support sustainable human resource practices, focusing on the distinct motivational drivers and value systems of various generations—Baby Boomers and Generations X, Y, Z, and Alpha. Worldwide trends show that employees' expectations regarding recruitment, selection, career development, and retention are becoming more diverse. Our research seeks to identify both the divergences and commonalities among these generational groups, as well as the strategies managers can apply to address their heterogeneous needs. To achieve this, the study employs a mixed-methods approach: it combines an extensive literature review with empirical data collection examining managerial motivation practices and their perceived effectiveness. The findings indicate that sustainable HR policy is grounded in the integration of generation-specific motivational techniques into organizational culture, alongside an adaptive, value-oriented reinterpretation of managerial roles. The study’s practical relevance lies in its recommendations for developing a managerial toolkit that strengthens intergenerational collaboration and supports the long-term enhancement of employee engagement, satisfaction, and performance.